The Feeding Potential of Greater Wax Moth (Galleria melonella) in Different Gauzes of Plastics - Dhakal, Sulav; Panthi, Susmita; Khanal, Bimala Kumari; Pandey, Laxmi; Bhattarai, Shiva Shankar (International Journal of Applied Sciences and Biotechnology, 2020)
Greater wax moth (Galleria mellonella), the honey comb moth, is the member of family pyralidae, considered as the serious pest of the bee industry, is also known for its plastics digesting ability. This research was carried out in two phases in the month of September- October & December- January. The data on change in weight of the plastics using digital balance and area of plastic consumed by the larvae was taken for 30 and 15 consecutive days in winter and summer respectively. From the statistical analysis the results found out; 8.4 mg, 2.4 mg & 1.6mg mean change in weight in the treatment T1, T2, T3 respectively; that the area of plastic consumed by the larvae was higher in plastics of 200 gauze i.e. smaller the gauze of plastic, greater the area consumed.  The study revealed the similar change in weight of plastics within the range of 300-500 gauze which was lower than the change in weight of the natural feed, wax. Higher rate of plastic feeding was observed in summer as compared to winter.Int. J. Appl. Sci. Biotechnol. Vol 8(2): 235-240